Chemical Oxygen Demand Removal Efficiency and Limited Factors Study of Aminosilicone Polymers in a Water Emulsion by Iron–Carbon Micro‐Electrolysis. (1st February 2014) - Yang, Shangyuan; Liang, Zhiwei; Yu, Huadong; Wang, Yunlong; Chen, Yingxu
ABSTRACT: : Micro‐electrolysis was applied in the present study to investigate the effect of pH, iron–carbon mass ratio, contact time, and treatment batch on the removal efficiency of chemical oxygen demand (COD) within an aminosilicone emulsion. The results exhibited that the removal efficiency of COD decreased linearly with the batch increase, and this tendency was consistent under the various conditions. The adsorption of activated carbons contributes a large portion to the elimination of COD within the aminosilicone emulsion. The oxidation action of iron–carbon micro‐electrolysis was proven and the aminosilicone emulsion's COD removal contribution was approximately 16%. Aminosilicone polymers were adsorbed on the surface of activated carbons and iron chips, which contributes to the decline of COD removal efficiency and limits the contribution of oxidation action.